Comparison Of Biology Learning Outcomes In The Talking Chips Type Cooperative Model With Snowball Throwing - Neneng Agustiningsih; Nur'aini Nur'aini; Nurdiana Nurdiana (PENBIOS: JURNAL PENDIDIKAN BIOLOGI DAN SAINS, 2022)
The type of this research is Quasi-Experimental Design. This research aim is whether there are differences in the cooperative model of talking chips and snowball throwing on student learning outcomes in biology subjects in class VIII in Bina Baru Hamlet, Wadukopa Village, Bima Regency. The purpose of this study was to find out the differences between talking chips and snowball-throwing learning models on student learning outcomes in the material for the human respiratory system for class VIII in Bina Baru Hamlet, Wadukopa Village, Bima Regency. The population in this study were all eighth-grade students in Bina Baru Hamlet, Wadukopa Village, Bima Regency as an experimental class using talking chips and snowball throwing learning models and control classes. The sampling technique in this study was a Quasi-Experimental Design. The instrument used to collect data is a test of learning outcomes in the form of multiple-choice questions, observation sheets, and lesson plans and the data collected is a type of quantitative data. The average learning outcomes of class students using the talking chips cooperative learning model and the snowball throwing type cooperative learning model of 81.6. This is shown from the significance value of the t-test of ˂ 0.05, it can be concluded that there is a significant effect of using the talking chips model with snowball throwing on the learning outcomes of class VIII students in Bina Baru Hamlet, Wadukopa Village, Bima Regency on the material of the human digestive system.